THE EFFECT OF NEW TECHNOLOGIES IN THE PROCESS OF LANGUAGE TEACHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
New technologies offer exciting possibilities for enhancing English language teaching and learning. In the ever-changing landscape of English language teaching , technology has emerged as a powerful ally for educators and learners alike. From mobile appliations to virtual reality, technology has not only enhanced the teaching experience but also made language learning more engaging and accessible to people around the globe. New technologies being introduced into education serve the increasing of the quality of the scholastic process and lead to positive results. The use of the technologies raises students’ interest to studying foreign language, forms their individual, creative abilities and corresponding skills.  Each student reveals his\her creative potential, skills and gifts for work on his\her own.